Santa Clara Valley prunes. - Gordon, John C. (photographer):::Creator::::::::::::
Stacks of cardboard boxes. Stamped on the boxes: "Santa Clara Valley prunes." "25 lbs. net weight. Hamlin brand Santa Clara Valley prunes. Packed by Hamlin Packing Co., San Jose, California."